The judicial system of the Turkestan ASSR (Journal of actual problems of jurisprudence, 2018)
In article features of emergence and functioning of judicial authorities which have special value and a role in a management system of the Turkestan SSR, founded April 30, 1918. Elevation of the Soviet Union suspended the functions of judicial institutions existing till this time in region of the Turkestan, in particular, the function of judicial districts, judicial chambers and all warships. Instead, they started functioning courts elected by democracy. According to reform, the basis of the bottom judicial system was made by world courts. In the beginning functions of local world judges carried out local councils, in particular, regional and district, and at their absence of their duty were assigned to the county, city and district courts and Councils of deputies of workers, soldiers and peasants. The development of judicial system of the Republic Turkestan was closely connected with Sharia which was formed in this area for centuries, politicians of the Russian Empire gradually disbanded courts of judge (biy) and promoted influence of the new judicial system introduced by Russia, establishment and further development of the Soviet power.Key words: management system, judicial authorities, customs, executive body, legislative activity, justice.